Developmental mechanisms of macroevolutionary change in the tetrapod axis: a case study of Sauropterygia - Soul, L; Benson, R (Wiley, 2017)
Understanding how developmental processes change on macroevolutionary timescales to generate body plan disparity is fundamental to the study of vertebrate evolution. Adult morphology of the vertebral column directly reflects the mechanisms that generate vertebral counts (somitogenesis) and their regionalisation (homeotic effects) during embryonic development. Sauropterygians were a group of Mesozoic marine reptiles that exhibited an extremely high disparity of presacral vertebral/somite counts. Using phylogenetic comparative methods, we demonstrate that somitogenesis and homeotic effects evolved in a co-ordinated way among sauropterygians, contrasting with the wider pattern in tetrapods, in which somitogenetic and homeotic shifts are uncorrelated. Changes in sauropterygian body proportions were primarily enabled by homeotic shifts, with a lesser, but important, contribution from differences in post-patterning growth among somites. High body plan plasticity was present in Triassic sauropterygians and was maintained among their Jurassic and Cretaceous descendants. The extreme disparity in the body plan of plesiosaurian sauropterygians did not result from accelerated rates of evolutionary change in neck length, but instead reflect this ancestral versatility of sauropterygian axial development. Our results highlight variation in modes of axial development among tetrapods, and show that heterogeneous statistical models can uncover novel macroevolutionary patterns for animal body plans and the developmental mechanisms that control them.